2020
DOI: 10.24018/ejfood.2020.2.4.76
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Content and Health Benefits of Bangladeshi Eggplant Ccultivars

Abstract: The investigation was conducted at the Olericulture Division, Bangladesh Agricultural Research Institute and the laboratory work was done at Vegetable Research Technology Section, Institute of Food Science and Technology, Bangladesh Council of Scientific and Industrial Research, Dhaka, Bangladesh during 2019-20 with ten types (Six- OP, four- Hybrid) of eggplant cultivar viz., BARI Begun-4, BARI Begun-6, BARI Begun- 8, BARI Begun-10, BARI Hybrid Begun-2, BARI Hybrid Begun-4, SM233, SM275, Hybrid 5x216 and Hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
4
16
0
Order By: Relevance
“…The average ascorbic acid concentration in the different landraces ranged from 3.46 to 18.47 mg 100 g −1 FW. These values are consistent with several studies carried out on eggplant landraces (Bidaramali et al, 2020 ; Quamruzzaman et al, 2020 ). Some studies, such as Prohens et al ( 2014 ) have even found major differences between traditional varieties and commercial hybrids, meaning that, on average, landraces present higher ascorbic acid content.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The average ascorbic acid concentration in the different landraces ranged from 3.46 to 18.47 mg 100 g −1 FW. These values are consistent with several studies carried out on eggplant landraces (Bidaramali et al, 2020 ; Quamruzzaman et al, 2020 ). Some studies, such as Prohens et al ( 2014 ) have even found major differences between traditional varieties and commercial hybrids, meaning that, on average, landraces present higher ascorbic acid content.…”
Section: Discussionsupporting
confidence: 92%
“…The fruit of the eggplant not only contains proteins, minerals, dietary fibre, minerals of interest as potassium, calcium, magnesium, sodium, iron (Quamruzzaman et al, 2020 ), but is also enriched in polyphenols, including phenolic acids such as chlorogenic acid, caffeic acid, and p -coumaric acid (Chumyam et al, 2013 ; Uscanga-Sosa et al, 2020 ), and flavonoids, including trace quantities of flavonols and a high content of various acylated and non-acylated anthocyanins specially in purple-coloured varieties (Koley et al, 2019 ). Also is appreciated for its content in other antioxidants as ascorbic acid (Fategbe et al, 2013 ) and vitamins, especially vitamin P (Dong et al, 2020 ), although has low provitamin A carotenoid content as compared to other Solanaceous crops such as tomatoes and peppers (Gürbüz et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Its antioxidant properties may reduce the risk of various cancers, protect against cardiovascular disease, and prevent acute respiratory infections [6,11,12]. Furthermore, eggplant fibers aid digestion by removing toxins and harmful materials from the stomach, lowering the risk of colon cancer [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Sekara (2010) recommended the 'Epic' F1 hybrid for field production in temperate climatic zone, as this cultivar achieved a mean marketable yield of 40 t/ha: the early production (first four harvests) accounted for 13.5% of the total yield. Several researchers observed significant difference among different eggplant cultivars for early and total yield (Cocker et al, 2018;Suleiman, 2020;Quamruzzaman et al, 2020). 'Sawad El Laiel' and 'Petra' showed minimum number days from transplanting to first harvest.…”
Section: Effect Of Production Systems Cultivarsmentioning
confidence: 99%
“…'Amedo' produced thickest fruit diameter in both seasons, while there were no significant differences in fruit length among 'Petra', ' Amedo' and 'Blackberry'in the first season and among all cultivars in the second season. Many researchers recorded genetic verbality in physical characters of eggplant fruit among cultivars by Samlindsujin et al (2017), Mahmoud and El-Mansy (2018), and Quamruzzaman et al (2020). Regarding the interaction between production system and cultivars, the greatest fruit weight and fruit diameter were noticed in 'Amedo' planted in open field in both seasons and in 'Sawad El Laiel' planted in open field in the first season and in the second season, respectively.…”
Section: Effect Of Production Systems Cultivarsmentioning
confidence: 99%